(untitled) (Journal of actual problems of jurisprudence, 2018)
The legal position is the responsibility of the lawyer to observe the rule of law. The legal position of the defense counsel is directly dependent on the position of his client. Even if the lawyer is sure that his client is guilty, and he insists on innocence, a lawyer in the exercise of protection should start from the position of his client’s innocence. The moral aspect of the position of a lawyer is the lawyer, first of all, should be guided by the interests of his client. Key words: law, law, lawyer, court, crime.